Peran Penyuluh Pertanian dan Pendapatan pada Usahatani Padi Sawah (Oryza Sativa) di Desa Anggoro Kecamatan Abuki Kabupaten Konawe - Darmawang Darmawang; Milawati Saranani; Abu Rahman (Pusat Riset dan Inovasi Nasional, 2024)
The location of this research was carried out in Anggoro Village, Abuki District, Konawe Regency with the consideration that the location is one of the centers of rice production in Abuki District. Seeing the large potential of rice farming in Anggoro Village, it is one of the prospects for developing rice farming so that it can have an impact on farmer welfare. Therefore, it is necessary to conduct research on farmers' assessments of the role of agricultural extension workers and farmer income. The sample determination was carried out by simple random sampling (sample random sampling) obtained as many as 60 farmer respondents from the total population. Based on the results of the research and discussion, it can be concluded: 1) The role of agricultural extension workers in Paddy Farming in Anggoro Village, Abuki District, Konawe Regency is considered quite good by respondent farmers, this is proven by the high average perception value based on each indicator of the role of agricultural extension workers. 2) The amount of income in paddy farming in Anggoro Village, Abuki District, Konawe Regency is obtained from the difference between total income and total production costs, resulting in an income of Rp. 4,685,383,001, - / planting season with an average of Rp. 78,089,717, - / planting season.